IMPLEMENTASI MUSIK SOLAWATAN TERHADAP PENURUNAN NYERI PADA KLIEN DENGAN HIPERTENSI - Muhammad Fandizal; Yuli Astuti; Dhien Novita Sani (Journal Prima Health Science, 2020)
Hypertension is an increase in blood pressure, which is the most influential risk factor for theincidence of heart and blood vessel disease. The incidence of hypertension on a national scale in thereporting of Riskesdas in 2013 obtained results of 25.8%, the lowest on the island of Papua at 16.8%,and the highest on the island of Bangka Belitung at 30.9%. As many as 25.8% of people withhypertension are only 1/3 diagnosed, and the remaining 2/3 are undiagnosed. Implementation of painreduction in hypertension can be done with auditory distraction techniques. This implementation canreduce pain from 6.6 to 5.1, with a significance of 0.001. The purpose of this study is to identify painreduction in clients with hypertension with the implementation of sholawat music (hearingdistraction). This research is a descriptive study with nursing care approach. The form of researchdesign used is the One-Shoot Case Study. The sampling technique used in this study is the noprobability sampling technique that is purposive sampling. This study was conducted on clients wholive in the village of Pondok Rangon in March - July 2019. The results of this study found a decreasein pain scale from moderate pain (scale 5 and 4) to zero scale (no pain) this decrease can be causedby shalawatan make the comfortable, calm and relaxed due to the release of endorphins. The use ofshalawatan music distraction as one of the implementations in nursing care can reduce or eliminatethe pain felt by the client.